2017
DOI: 10.1111/acem.13115
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Pretreatment Reduces the Discomfort of Intranasal Midazolam Administration: A Randomized, Double‐blind, Placebo‐controlled Trial

Abstract: Objective Intranasal (IN) midazolam is a commonly prescribed medication for pediatric sedation and anxiolysis. One of its most frequently encountered adverse effects is discomfort with administration. While it has been proposed that premedicating with lidocaine reduces this undesirable consequence, this combination has not been thoroughly researched. The objective of our study was to assess whether topical lidocaine lessens the discomfort associated with IN midazolam administration. Methods This was a double‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…4 Additionally, previous studies have shown that preadministered and coadministered lidocaine are more effective than placebo in decreasing pain and distress associated with intranasal administration of midazolam or acidic solutions in both children and adults. 7,8 The mean scores of pain and distress associated with intranasal midazolam administration observed in both groups of children who received preadministered and coadministered lidocaine were not scores that typically represent no pain or mild pain. [9][10][11][12] This differs from a previous study of children aged 5 to 50 months who received intranasal lidocaine before intranasal midazolam and whose parents assigned pain scores associated with intranasal midazolam administration that were no >2 out of 10.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…4 Additionally, previous studies have shown that preadministered and coadministered lidocaine are more effective than placebo in decreasing pain and distress associated with intranasal administration of midazolam or acidic solutions in both children and adults. 7,8 The mean scores of pain and distress associated with intranasal midazolam administration observed in both groups of children who received preadministered and coadministered lidocaine were not scores that typically represent no pain or mild pain. [9][10][11][12] This differs from a previous study of children aged 5 to 50 months who received intranasal lidocaine before intranasal midazolam and whose parents assigned pain scores associated with intranasal midazolam administration that were no >2 out of 10.…”
Section: Discussionmentioning
confidence: 95%
“…[4][5][6] The pain and distress associated with intranasal midazolam administration can be decreased by using intranasal lidocaine. [5][6][7] One method involves medicating with intranasal lidocaine before intranasal midazolam administration (preadministered lidocaine), which requires 2 separate administrations. [5][6][7][8] A second method involves mixing the lidocaine and midazolam and administering the premixed solution (coadministered lidocaine), which requires only a single administration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations